Description of the previously unknown male of Systropha (Austrosystropha) macronasuta (Hymenoptera: Halictidae: Rophitinae) from Kenya - Bossert, Silas; Patiny, Sébastien (Journal of Melittology, 2017)
We describe and illustrate for the first time the previously unknown male of Systropha (Austrosystropha) macronasuta Strand. We provide a species diagnosis and modified couplets of the recent identification key to allow for easy identification of this sex. Based on the first record of S. macronasuta from the African mainland, we discuss the distribution of the species.